2009
DOI: 10.1029/2009gl037987
|View full text |Cite
|
Sign up to set email alerts
|

Warming in the Agulhas Current system since the 1980's

Abstract: International audienceSince the 1980's, the sea surface temperature of the Agulhas Current system has increased significantly. The warming is due to an augmentation of its transport in response to an increase in wind stress curl in the South Indian Ocean at relevant latitudes. This causes an increase in the fluxes of salt and heat into the Atlantic Ocean and in the transfer of energy from the ocean to the atmosphere. Therefore, the changes we are witnessing in the region could have far reaching consequences on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
168
1
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(192 citation statements)
references
References 27 publications
17
168
1
3
Order By: Relevance
“…[22] In addition, the Mozambique Channel is the source of the Agulhas Current, the most intense western boundary current in the Southern Hemisphere, which plays an important role in the climate of Southern Africa and acts as a source of heat and salt to the Atlantic Ocean [Backeberg et al, 2012;Rouault et al, 2009]. There is evidence of the formation of an anticyclonic eddy in the northern section of the channel during the boreal winter that subsequently moves southward advecting subtropical waters into the Agulhas Current [Schouten et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] In addition, the Mozambique Channel is the source of the Agulhas Current, the most intense western boundary current in the Southern Hemisphere, which plays an important role in the climate of Southern Africa and acts as a source of heat and salt to the Atlantic Ocean [Backeberg et al, 2012;Rouault et al, 2009]. There is evidence of the formation of an anticyclonic eddy in the northern section of the channel during the boreal winter that subsequently moves southward advecting subtropical waters into the Agulhas Current [Schouten et al, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the background environment are however such as to place the flow close to the point where this bifurcation vanishes. There is evidence of a trend toward an intensification of the easterly trade winds over the southern Indian Ocean [Han et al, 2010;Rouault et al, 2009] and such changes would result in a decrease in the inverse Rossby number that may result in changes in the flow splitting by Madagascar.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we explore the possibility that remote forcing from outside the tropical Atlantic Ocean, namely, because of increased Agulhas leakage transport south of Africa (Rouault et al 2009;Biastoch et al 2009), has led to the warming of the subsurface tropical Atlantic. These tropical Atlantic subsurface waters, which are warmer than in previous decades, are subsequently upwelled to the surface by the increased trade winds, resulting in the observed warming trend at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest Eulerian approach assumes that the waters of Indian Ocean origin represent the warmest and most saline waters across the Goodhope section. These thermohaline properties can then be utilised in order to establish an integration domain over which volume transport is calculated (Rouault et al 2009). The limitation of such an approach is that by imposing water mass criteria, the leakage in eddy-rich regions may be underestimated, although similar methods have been shown to reproduce the variability well (van Sebille et al 2010b;Loveday et al 2014;Putrasahan et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This should be considered a first step to verify whether coarser resolution ocean models hence climate models are able to reproduce the processes of variability of AL. Rouault et al (2009) and Biastoch et al (2009) identified evidence that AL is increasing with climate change, linked to a warming trend in the Agulhas system since the 1960s and southward shift of the Subtropical front. Over 2-4 decades the warm salty water that enters the South Atlantic is advected northwards (Ruhs et al 2013;Weijer et al 2001), its influence on the buoyancy balance affects deep water formation, the AMOC and thus global climate.…”
Section: Introductionmentioning
confidence: 99%